Out-Group Penalties in Refugee Assistance: A Survey Experiment - Cristina Cattaneo; Daniela Gireco; Nicola Lacetera; Mario Macis (Center for Economic Studies and ifo Institute (CESifo), 2024)
We study out-group biases in attitudes toward refugees, and the effect of European Union (EU) immigration policies on these views, using an online survey experiment including 4,087 Italian participants. We assess attitudes using donations to a randomly assigned group: Italian victims of violence or refugees fleeing wars in Ukraine or African countries. We also employ a novel measure, the share donated in cash. While donations indicated less support for African and Ukrainian refugees compared to Italian victims, the cash measure revealed a stronger prejudice against distant out-groups, with participants giving African refugees a smaller proportion of cash donations. This result was mainly driven by individuals with right-leaning political views. Providing information about immigration policy reforms that give the EU a more substantial role in receiving and allocating refugees had no impact. Textual analysis supports these findings.
Keywords: C99; D02; D64; J15; 330; ingroup-outgroup relations; prejudice; refugees; EU immigration policies; survey experiments